Supporting electrolyte interaction with the AACVD synthesized Rh thin film influences the OER activity. (5th August 2022) - Hasan, Md Mahedi; Islam, Tamanna; Shah, Syed Shaheen; Aziz, Md. Abdul; Awal, Abdul; Hossain, Md. Delwar; Ehsan, Muhammad Ali; Ahammad, A.J. Saleh
Abstract: Electrocatalytic oxygen evolution reaction (OER) is one of the most promising candidates for the sustainable energy. This has led researchers to focus towards developing highly active electrocatalysts. Our work takes a wholistic approach to understanding the key factors that influence the OER process. We focused on preparing a metallic electrocatalyst and tested out its OER performance using two different supporting electrolytes. We also studied the effect of crystal planes of the electrocatalyst on the OER process using computational simulation (CS) methods. For this, rhodium (Rh) thin film (RhTF) electrocatalysts on indium tin oxide (RhTF_ITO) were fabricated for OER through aerosol assisted chemical vapor deposition (AACVD). The prepared electrodes showed excellent electrocatalytic activity for OER (for 10 mA/cm 2 η = 273 mV in 1.0 M KOH). The effect of the supporting electrolytes and the crystal planes of RhTF electrodes were analyzed using electroanalytical techniques and CS methods. Tafel slope (TS) analysis revealed that electron transfer kinetics was slower for the NaOH compared to the KOH. The scan rate (ν) analysis indicated that there is weak electrostatic interaction between the hydrated outer Helmholtz plane (OHP) of Na + and K + ions with the adsorbed OH(ad) that impacts the OER process. With increasing ν the restructuring of the electrochemical double layer (EDL) increases resulting in similar OER performance for both the supporting electrolytes. The micro-kinetic analysis showed that the rate determining step (RDS) for NaOH and KOH required around 1.67 eV and 1.07 eV. The density functional theory (DFT) analysis revealed that these energy values are closest to the Rh (111) plane reaction pathway. Adsorption locator (AL) analysis further revealed that the hydrated cations could directly get adsorbed on the Rh crystal planes hindering the electron transfer (ET) in the OER process. The DFT analysis further revealed that the lowest energy pathway for the OER process is followed on the Rh (220) plane. These analyses demonstrated that it is possible to fine tune the OER using supporting electrolyte and electrocatalysts that can work synergistically for getting the optimal OER performance. Graphical abstract: Image 1 Highlights: Synthesis of seaweed like metallic Rh TF through AACVD method. Supporting electrolyte significantly impacts OER performance of electrocatalysts. The hydrated cations (K + and Na + ) are responsible for this difference in OER performance. The Rh (220) crystal plane shows the lowest energy pathway for the OER process. The total energy of the crystal planes determine how they would interact with the hydrated cations.